An analyis of internal communication factors influencing the implementation of business process reengineering (BPR) in the bank - Ali, Mass Hareeza (2009)
This research focuses on the factors that affect the successful implementation of BPR in the ACB bank in Malaysia. The real name of the bank had been disguised. The views and perceptions of employees of the bank are presented in the form of data gathered through questionnaires. Information concerning particular aspects of bank procedure was also included. Factor concern is on internal communication in the organization particularly the bank. This study will analyze the importance of all stated are a within internal communication factors in implementation of BPR in the participated bank in Malaysia. Results from the research were expected to contribute new information in the development criteria and things need to be concerned of any changes within the internal communication in Malaysian banking sector.